PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN DI RUMAH SAKIT ISLAM KOTA MAGELANG - Putri, Happy Ayuningrum; Saryadi, Saryadi; Dewi, Reni Shinta (Jurnal Ilmu Administrasi Bisnis, 2013)
This research purpose to find out influence of service quality on hospitalized patient satisfaction at Islamic Hospital Magelang City. This research included in explanatory. Taked 100 respondents as sample with stratified proportionate random sampling method. Collecting data used questionnaire. Hypotheses tested by correlation coefficient, simple linear regression, multiple linear regression, t test, F test, and determination coefficient. The result of this research show that realibility dimension have significant influence to patient satisfaction, responsiveness dimension have significant influence to patient satisfaction, assurance dimension have significant influence to patient satisfaction, empathy dimension have significant influence to patient satisfaction, tangibles dimension have significant influence to patient satisfaction. Realibility, responsiveness, assurance, empathy, and tangibles dimension in partial and simultaneous have significant influence to patient satisfaction.